Gestão de custos na construção civil - Pio, Jamille Alencar (2017)
Organizations are increasingly concerned with reducing their production costs to maximize profits, and Cost Management plays a crucial role in this process for any organization and business. Therefore, due to its interdisciplinary nature, Transaction Cost Economics, combined with Cost Management, which is in the position of promoting methodologies and procedures, must receive special attention from various business sectors to provide the necessary adaptations for promoting better financial results for institutions. The Construction sector, due to its peculiarities, stands out as an area where cost management becomes vital. Therefore, this research aims to characterize the practice of Cost Management in the Construction sector in the city of Fortaleza. Classified as qualitative, this study employs the Case Study strategy with multiple cases, in which information from a group of companies in Fortaleza operating throughout the State of Ceará will be analyzed. The information was collected through interviews with key actors in the cost management of the analyzed companies, using a semi-structured questionnaire. For data analysis, content analysis techniques and a repertoire grid will be employed. To ensure greater rigor in the analysis of results, the software Nvivo10 will also be used, providing greater security in structuring the collected data for analysis.